A real-world, non-interventional Indian study on clinical assessment of intense moisturizing formulation in dry skin disorders - Dhoot, Dhiraj S.; Mahadkar, Namrata; Barkate, Hanmant (International Journal of Research in Dermatology, 2021)
Introduction: Moisturizers account for the largest and important skin care product categories and are the backbone in the management of dry skin conditions associated with atopic dermatitis (AD), psoriasis and ichthyosis. Methods: A multicentre, retrospective data analysis was done at 145 dermatology clinics across India in patients who were prescribed MaxRich®. Patients with history of xerosis with an identifiable causes like atopic dermatitis, psoriasis and ichthyosis were included in study. Effectiveness data in terms of improvement in Dry Skin Area and Severity Index (DASI) Score compared to baseline and physician global assessment at the end of treatment for improvement in xerosis were captured. Results: There was significant reduction in mean DASI score as compared to baseline at week 2 & 4 (p<0.01). As compared to baseline, a significant decrease in DASI score was observed by 47.7% and 82.4% at the end of week 2 and 4 respectively. As per physician global assessment, 458 patients (83.4%) noticed very good improvement in xerosis at the end of 4 weeks whereas 82 patients (14.9%) recorded moderate improvement. Similar results were also obtained for patient global assessment where 478 patients (87%) recorded very good improvement; 67 patients (12.2%) and 6 patients (1.1%) recorded moderate and mild improvement respectively. There were no adverse events reported with MaxRich®. Conclusion: MaxRich®, an intense moisturizer was effective in improvement of DASI score associated with atopic dermatitis, psoriasis and ichthyosis and can be considered as an adjunct therapy in the management of these skin disorders for better results.